The Challenges Facing Training in Pediatric Surgery Worldwide - Beasley, Spencer W. (Frontiers in Pediatrics, 2013)
Those involved in the administration and delivery of training programmes in paediatric surgery have to accommodate the increasing complexity of the specialty as well as the difficulties associated with providing trainees sufficient exposure to clinical material that they can develop the competencies and skills required. In addition, recent restrictions imposed on many health systems have not always been in the best interests of trainees or their surgical teachers. This paper outlines four of the current challenges faced by training boards in paediatric surgery worldwide: (1) exposure to rare and index cases, mostly congenital structural abnormalities of surgical significance; (2) governance of surgical training programmes and the level of supervision that can be provided to trainees; (3) provision of an adequate workforce distributed according to the needs of the population; and (4) support to emerging (and usually grossly under-resourced) countries. This review documents the implications of each of these issues for the future training of paediatric surgeons.